Pengembangan Bahan Ajar IPA Terpadu Berbasis Android Berorientasi Keterampilan Berpikir Kritis - Maulida, Hilda; Sinaga, Parlindungan; Susilawati, Mrs. (Institut Pendidikan Indonesia, 2019)
Abstract - The results of the preliminary study show that students have low critical thinking skills. Teachingmaterials have an important role in learning. Learning cannot be done without teaching materials. This studyaims to (1) develop teaching materials in the form of android applications with the development model of theTeaching Material Writing Process Model (MPM2A), (2) determine the feasibility of teaching materials, (3)the effectiveness of teaching materials in improving students' critical thinking skills. This type of research isresearch and development (RnD) and to test the effectiveness of teaching materials. This study uses the QuasiExperiment design using pretest-posttest control group design in one of the state junior high schools in thecity of Bandung. The study sample consisted of 64 students. With 32 students in the experimental class and32 students in the control class. Research results 1) based on the feasibility test of teaching materialsdeveloped appropriate for use in learning activities. 2) teaching materials can improve critical thinking skillsin the medium category 3) a measure of the effect size that teaching materials developed are effective inimproving critical thinking skillsKeywords: Teaching materials, Android, Integrated Science, Critical Thinking SkillsAbstrak - Hasil studi pendahuluan memperlihatkan bahwa siswa memiliki keterampilan berpikir kritis yangrendah. Bahan ajar memiliki peranan penting dalam pembelajaran. Pembelajaran tidak dapat dilakukan tanpabahan ajar. Penelitian ini bertujuan untuk (1) mengembangkan bahan ajar dalam bentuk aplikasi androiddengan model pengembangan Model Proses Menulis Materi Ajar (MPM2A), (2) mengetahui kelayakanbahan ajar, (3) keefektifan bahan ajar dalam meningkatkan keterampilan berpikir kritis siswa. Jenis penelitianini adah penelitian dan pengembangan (RnD) dan untuk menguji keefektifan bahan ajar Penelitian inimenggunakan desain Quasi Eksperimen dengan menggunakan pretest-posttest control group design di salahsatu SMP Negeri di Kota Bandung. Sampel penelitian terdiri atas 64 siswa. Dengan 32 siswa kelaseksperimen dan 32 siswa kelas kontrol. Hasil penelitian 1) berdasarkan uji kelayakan bahan ajar yangdikembangkan layak untuk digunakan dalam kegiatan pembelajaran. 2) bahan ajar dapat meningkatkanketerampilan berpikir kritis pada kategori sedang 3) ukuran dari effect size bahwa bahan ajar yangdikembangkan efektif dalam meningkatkan keterampilan berpikir kritis.Kata kunci: Bahan ajar, Android, IPA Terpadu, Keterampilan Berpikir Kritis